Formulasi dan Karakterisasi Jamu Serbuk Instan Tinospora crispa dan Citrus aurantifolia dengan Eksipien Taste Masking - Rosyfiana Syafi'i Salma; Nawafila Februyani; Abdul Basith (Journal of Pharmaceutical and Sciences, 2026)
Tinospora crispa has a dominant bitter taste and therefore requires formulation strategies to improve palatability. This preliminary study formulated instant herbal powder containing Tinospora crispa and Citrus aurantifolia with graded ratios of maltodextrin and sucrose and evaluated its initial physical characteristics and exploratory sensory response. A one-factor completely randomized design comprised three formulas, each prepared in triplicate for physical testing. Evaluations included organoleptic properties, visual homogeneity, flow time, flow rate, angle of repose, moisture content, dissolution time, pH, and an exploratory hedonic assessment involving seven untrained panelists. Numerical physical data were analyzed by one-way ANOVA followed by Tukey HSD when significant, while sensory scores were analyzed using the Friedman test followed by Wilcoxon signed-rank tests with Bonferroni correction. All formulas were fine, visually homogeneous powders with a pH of 5 and moisture content of 2.50-3.67%. The excipient ratio significantly affected angle of repose and moisture content. Friedman testing indicated global differences in taste and overall acceptance, but no formula pair remained significant after Bonferroni correction. No single formula was optimal across all physical parameters. F3 showed the highest descriptive scores for taste and overall acceptance and the fastest flow time, but this tendency cannot be generalized because of the small exploratory panel and incomplete raw-material, chemical, particle-size, and stability characterization.